Internet utilization and access for vocational school teachers at during the covid-19 pandemic - Saripudin, S; Sumarto, Sumarto; Juanda, E A (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2023)
The aim of this study is to find out the utilization of the internet and the internet access of vocational teachers at the vocational schools during the COVID-19 pandemic. The research uses a descriptive quantitative method and the research instrument used was a set of questionnaires distributed to 267 vocational school teachers in West Java before and during the COVID-19 pandemic. The research variables include the utilization aspects and the vocational teachers' access to the internet at home and at school in searching for learning material resources. The data obtained were analysed using statistical analysis.. Results show that 82% of teachers used the internet to find the subject-related resources, 66% possessed teleconferencing facilities, 63% already had internet connections at home. Furthermore, teachers' internet usage frequency during the COVID-19 pandemic was higher than before COVID-19. Teachers who work from home used the internet longer during the COVID-19 pandemic; more than 5 hours a day, compared to pre-COVID-19; which was 1-2 hours. Teachers who work from school also used the internet 3-4 hours longer during the COVID-19 than prior to the COVID-19 pandemic, which was around 1-2 hours.